What Factors Affect The Undergraduate Experiences of Student Veterans? - Thompson-Ebanks, Valerie; Ginn, Hannah; Valentine, Deborah (Advances in Social Sciences Research Journal, 2017)
This study adds to the existing body of knowledge about the university experiences of undergraduate student veterans. Vacchi and Berger’s (2014) Model of Student Veteran Support provides the conceptualizing framework that examines a university’s efforts to foster the success of student veterans. This study uses qualitative methods to identify factors that support and impede the success of student veterans in higher education. Key findings that could have significant implications for faculty, and higher education administrators are discussed.